Feasibility and Reliability of Quantifying Passive Muscle Stiffness in Young Children Using Shear Wave Ultrasound Elastography - Brandenburg, Joline E. (J Ultrasound Med, 2015)
OBJECTIVE: To investigate the feasibility and reliability of passive muscle stiffness measurements in children through use of shear wave ultrasound elastography. METHODS: This is a prospective cross -sectional study quantifying the passive stiffness of bilateral lateral gastrocnemii muscles during passive stretch in twenty typically developing children (age range, 2.0–12.6 years). Data collected included passive stiffness of the lateral gastrocnemius muscle (shear modulus in kilopascal [kPa]) at four positions of progressive passive foot dorsiflexion; demographic characteristics of the child participants; and comparison of demographic characteristics with the shear modulus. RESULTS: Passive stiffness increased with increasing stretch (mean [SD] range of stretch, 7.1 [2.0]–36.2 [22.0] kPa). For all four foot positions, no significant difference was found between right and left legs (range P=0.42 to P=0.98) or between the sexes (range P=0.28 to P> 0.99). No correlation of passive muscle stiffness to age, body mass index, or ankle range of motion was found. Reliability of measurements was good to excellent (mean [95% CI] range of reliability 0.67 [0.44–0.83] to 0.80 [0.63–0.90]). CONCLUSIONS: Measurements of passive stiffness of the lateral gastrocnemius muscle are feasible and reliable in children as young as 2 years. Because the present study found no significant difference between sex and the side tested in this age-group, future studies involving children of this age range may not need to be stratified on the basis of these parameters. Defining normal passive muscle stiffness in children is critical for identifying and understanding the implications of abnormal passive muscle stiffness in children with neuromuscular disorders.